Advisors as key partners for achieving adoption at scale: embedding “My Climate View” into agricultural advisory networks - Jakku, Emma; Fleming, Aysha; Fielke, Simon; Snow, Stephen; Malakar, Yuwan; Cornish, Gillian; Hay, Rachel; Williams, Liana (Frontiers in Sustainable Food Systems, 2024)
This paper examines the role of agricultural advisors as key partners for scaling adoption of long-term climate information. Agri-food sectors across the world face significant challenges in responding to climate change, which intersect with broader pressures driving transitions to more climate resilient and sustainable agri-food systems. Making better climate information available to farmers is a key part of responding to these challenges, since relevant and usable climate information can help farmers to adapt to future climate conditions. The development of climate services, which seek to provide climate information to assist with decision making, has therefore increased significantly over the last decade. The Climate Services for Agriculture (CSA) program provides long-term climate projections to help the Australian agriculture sector prepare for and adapt to future climate conditions. ‘My Climate View’ is an online tool produced by CSA, which provides localised and contextualised, commodity-specific climate information, through historic weather data and multi-decadal projections of future climate, aimed at Australian famers and farm advisors. Agricultural advisors have a critical yet often underutilised role as climate information intermediaries, through assisting farmers translate climate information into action. This paper uses CSA as a case study to examine farmer-advisor interactions as a key adoption pathway for My Climate View. Interactions between farmers and their trusted advisors are an essential part of the enabling environment required to ensure that this long-term climate information can be used at the farm scale to inform longer-term decisions about climate adaptation. We use the concept of an interaction space to investigate farmer-advisor interactions in the adoption and sustained use of My Climate View. We interviewed 52 farmers and 24 advisors across Australia to examine the role of advisors as key partners in helping farmers to understand climate information and explore on-farm climate adaptation options. We find that although My Climate View is not a transformational technology on its own, its ability to enable farmers and advisors to explore and discuss future climate conditions and consider climate adaptation options has the potential to support transformational changes on-farm that are needed to meet the sustainability transition pressures that climate change presents.